2008
DOI: 10.1111/j.1525-1446.2008.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Who Are the Pregnant Adolescents in the Poorest State Capital of Brazil?

Abstract: Adolescent pregnancies are likely to have an unfavorable long-term impact on adolescent mothers' lifestyle, even with some improvement since 1996. Effective programs for adolescent pregnancy prevention are needed to reduce the possibility of continuance of these trends for another 10 or more years in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
1
4
0
8
Order By: Relevance
“…Adolescents who lived with a partner were in the majority, a result consistent with other studies (12,18,19) . Research conducted with pregnant adolescents in the city of Teresina showed that, among young women who lived with a partner, 30.7% remained financially (12,13) . Thus, the early marriages may place the young people in a more difficult socio-economic situation, especially when the partner is also an adolescent and/or unemployed, making them more vulnerable to other conditions of social risk.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Adolescents who lived with a partner were in the majority, a result consistent with other studies (12,18,19) . Research conducted with pregnant adolescents in the city of Teresina showed that, among young women who lived with a partner, 30.7% remained financially (12,13) . Thus, the early marriages may place the young people in a more difficult socio-economic situation, especially when the partner is also an adolescent and/or unemployed, making them more vulnerable to other conditions of social risk.…”
Section: Discussionsupporting
confidence: 80%
“…We observed a significant number adolescents who did not attend school, confirming that the pregnancy and the birth of a child are important causes of isolation and difficulty in studies among adolescents (12) . The high proportion of adolescents with education ranging from illiteracy to not completing elementary school, demonstrates the reduced level of instruction prevalent across the young women surveyed.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…A gravidez consiste em fenômeno peculiar ao desenvolvimento humano normal, entretanto, este mesmo fenômeno pode levar a sérias complicações quando ocorre na juventude 1,2 . A gestação nesta etapa evolutiva da vida interfere nas representações sociais das jovens, por meio da súbita passagem do papel de filha e ser dependente para o papel de mãe e provedora.…”
Section: Introductionunclassified